Drug Repositioning in Friedreich Ataxia - Rufini, Alessandra; Malisan, Florence; Condò, Ivano; Testi, Roberto (Frontiers in Neuroscience, 2022)
Friedreich ataxia is a rare neurodegenerative disorder caused by insufficient levels of the essential mitochondrial protein frataxin. It is a severely debilitating disease that significantly impacts the quality of life of affected patients and reduces their life expectancy, however an adequate cure is not yet available for patients. Frataxin function, although not thoroughly elucidated, is associated with assembly of iron-sulfur cluster and iron metabolism, therefore insufficient frataxin levels lead to reduced activity of many mitochondrial enzymes involved in the electron transport chain, impaired mitochondrial metabolism, reduced ATP production and inefficient anti-oxidant response. As a consequence, neurons progressively die and patients progressively lose their ability to coordinate movement and perform daily activities. Therapeutic strategies aim at restoring sufficient frataxin levels or at correcting some of the downstream consequences of frataxin deficiency. However, the classical pathways of drug discovery are challenging, require a significant amount of resources and time to reach the final approval, and present a high failure rate. Drug repositioning represents a viable alternative to boost the identification of a therapy, particularly for rare diseases where resources are often limited. In this review we will describe recent efforts aimed at the identification of a therapy for Friedreich ataxia through drug repositioning, and discuss the limitation of such strategies.